2023
DOI: 10.3390/jof9070770
|View full text |Cite
|
Sign up to set email alerts
|

Candida palmioleophila: A New Emerging Threat in Brazil?

Gisela Lara da Costa,
Melyssa Negri,
Rodrigo Prado Rodrigues de Miranda
et al.

Abstract: Human activity directly or indirectly causes climate change, promoting changes in the composition of the atmosphere. This change is beyond the variation of the natural climate. In this manner, climate change could create an environmental pressure which is enough to trigger new fungal diseases. In addition to climate alterations, the onset of the COVID-19 pandemic has also been associated with the emergence of fungal pathogens. Fungi showed that an inability to grow at high temperatures limits the capacity of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Additionally, most of the wrongly identified strains showed a resistant antifungal profile, such as C. haemulonii, C. ciferri, and C. rugosa, reinforcing the importance of correct identification. It is important to mention that our group published a study [52] using C. palmioleophila isolates that showed a characteristic MIC indicating resistance to fluconazole, corroborating the findings of the authors that point out that resistance to some azole derivatives among species of the Saccharomycotina subphylum, in which Candida species are inserted, is associated with multifactorial circumstances, such as indiscriminate exposure to azoles, patient profiles, geographic location of the species and genetic particularities [53,54].…”
Section: Esg22 -C Tropicalissupporting
confidence: 83%
“…Additionally, most of the wrongly identified strains showed a resistant antifungal profile, such as C. haemulonii, C. ciferri, and C. rugosa, reinforcing the importance of correct identification. It is important to mention that our group published a study [52] using C. palmioleophila isolates that showed a characteristic MIC indicating resistance to fluconazole, corroborating the findings of the authors that point out that resistance to some azole derivatives among species of the Saccharomycotina subphylum, in which Candida species are inserted, is associated with multifactorial circumstances, such as indiscriminate exposure to azoles, patient profiles, geographic location of the species and genetic particularities [53,54].…”
Section: Esg22 -C Tropicalissupporting
confidence: 83%
“…Environmental and human-induced factors are greatly impacting the evolution, selection, and adaptation of previously harmless fungal species, which are now posing a growing threat to the health of humans and animals [ 32 ]. This is the case for Candida viswanathii , C. auris , C. blankii , C. palmioleophila , C. vulturna , C. massiliensis , Trichophyton indotineae , Pseudogymnoascus destructans , Batrachochytrium dendrobatidis , and Kodamaea ohmeri , all of which are environmental fungi that have been successfully adapted to animals or humans over time [ 12 , 18 , 31 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, as this system can identify up to 50 different yeasts, including K. ohmeri . However, it has been observed that in this identification system, certain isolates of Candida palmioleophila can be mistakenly identified as K. ohmeri [ 33 ]. The BD Phoenix BD Phoenix TM yeast identification system, on the other hand, could not correctly identify any isolate.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental and human-induced factors are greatly impacting the evolution, selection, and adaptation of previously harmless fungal species, which are now posing a growing threat to the health of humans and animals [32]. This is the case for Candida viswanathii, C. auris, C. blankii, C. palmioleophila, C. vulturna, C. massiliensis, Trichophyton indotineae, Pseudogymnoascus destructans, Batrachochytrium dendrobatidis, and Kodamaea ohmeri, all of which are environmental fungi that have been successfully adapted to animals or humans over time [12,18,31,[33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%